Simulation-based multi-objective optimization of side-hull arrangement applied to an inverted-bow trimaran ship at cruise and sprint speeds. Issue 2 (1st February 2023) - Nazemian, Amin; Ghadimi, Parviz
Abstract : Numerical optimization of an inverted-bow trimaran is carried out through three simulation-based design (SBD) frameworks. Different positions of the trimaran's side hull are investigated based on a computational fluid dynamics solver using the non-dominated sorting genetic algorithm-III (NSGA-III), simultaneous hybrid exploration that is robust, progressive and adaptive (SHERPA) and response surface (RS) multi-objective optimization for resistance at cruise and sprint speeds. The aims are to create and develop a convenient tool for optimization and investigate the appropriate position of the side hull. An automated, low-cost optimization platform is achieved that can be implemented in other maritime projects. A 10.5% drag reduction for cruise speed and 6.6% reduction for sprint are obtained, corresponding to lower longitudinal and large transversal distances of the side hull. SHERPA and NSGA-III produce the same results, but SHERPA is 2.5 times faster than NSGA-III. RS obtains less desirable results, but in the lowest central processing unit time.